2021
DOI: 10.3233/jad-201344
|View full text |Cite
|
Sign up to set email alerts
|

In vitro Characterization of the Regional Binding Distribution of Amyloid PET Tracer Florbetaben and the Glia Tracers Deprenyl and PK11195 in Autopsy Alzheimer’s Brain Tissue

Abstract: Background: Emerging evidence indicates a central role of gliosis in Alzheimer’s disease (AD) pathophysiology. However, the regional distribution and interaction of astrogliosis and microgliosis in association with amyloid-β (Aβ) still remain uncertain. Objective: Here we studied the pathological profiles in autopsy AD brain by using specific imaging tracers. Methods: Autopsy brain tissues of AD (n = 15, age 70.4±8.5 years) and control cases (n = 12, age 76.6±10.9) were examined with homogenate binding assays,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
48
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 36 publications
(49 citation statements)
references
References 105 publications
1
48
0
Order By: Relevance
“…However, recent clinical study with [ 11 C]ER176 ( 105 ) and [ 11 C]GE-180 ( 88 ) demonstrated a significant decrease in ligand retention in low-affinity binders, suggesting the necessity of further in vivo examination. Second, the heterogenous cellular sources of TSPO PET tracers have been demonstrated in astrocytes, endothelial cells, and vascular smooth muscle cells, in addition to microglia in both patients with AD and animal models ( 61 , 85 , 86 , 193 , 226 229 ) ( Figures 1A, B ) . Although conventional opinions consider microglia as major cellular source of TSPO in the central nervous system, latest study finds vascular TSPO provides major binding sites for TSPO ligands including most widely used [ 11 C]PK11195 and [ 11 C]PBR28 in normal mouse brains ( 57 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, recent clinical study with [ 11 C]ER176 ( 105 ) and [ 11 C]GE-180 ( 88 ) demonstrated a significant decrease in ligand retention in low-affinity binders, suggesting the necessity of further in vivo examination. Second, the heterogenous cellular sources of TSPO PET tracers have been demonstrated in astrocytes, endothelial cells, and vascular smooth muscle cells, in addition to microglia in both patients with AD and animal models ( 61 , 85 , 86 , 193 , 226 229 ) ( Figures 1A, B ) . Although conventional opinions consider microglia as major cellular source of TSPO in the central nervous system, latest study finds vascular TSPO provides major binding sites for TSPO ligands including most widely used [ 11 C]PK11195 and [ 11 C]PBR28 in normal mouse brains ( 57 ).…”
Section: Discussionmentioning
confidence: 99%
“…A few second generation tracers including [ 11 C]DAA1106, [ 1( F]FEDAA1106, [ 125 I]CLINDE [ 11 C]PBR06, [ 11 C]PBR28, [ 18 F]PBR111, [ 18 F]DPA-713, [ 18 F]DPA-714, [ 18 F]F-DPA, [ 11 C]AC-5216, [ 18 F]FEMPA, and [ 18 F]FEPPA have been developed to overcome the limitations of [ 11 C]PK11195 ( 45 , 46 , 52 , 61 63 , 66 , 69 71 , 83 , 84 , 197 ) ( Table 1 ). However, the binding affinities of second generation TSPO tracers in human brain differ based on the rs6971 polymorphisms, which introduces higher variability between subjects ( 45 , 46 , 52 , 61 63 , 66 , 69 71 , 197 ). In addition, the [ 11 C]PBR28 binding appears to be affected by chromosome 1 variant rs2997325 on microglial activation ( 198 ).…”
Section: Neuroinflammation Positron Emission Tomography Imagingmentioning
confidence: 99%
See 1 more Smart Citation
“…Though, we observed a percentage of binding to bovine serum albumin that is a plasma protein in the circulation and found in Aβ plaques. This is a common phenomenon of Aβ binding probes such as BTA-1, PIB, florbetaben, florbetapir etc [ [71] , [72] , [73] , [74] ]. Co-staining of CRANAD-2 to brain sections from arcAβ mice with 6E10/OC antibodies of Aβ deposition clearly showed close resemblance in both vascular and parenchymal Aβ deposits.…”
Section: Discussionmentioning
confidence: 99%
“…Translocator protein (TSPO) is the most widely used neuroinflammation target for PET imaging. [16][17][18][19][20][21][22][23][24][25][26][27], have been evaluated in (pre-)clinical studies. PET imaging studies using TSPO tracers have shown increased brain uptake in post-stroke, although different time course and distribution were detected depending on the animal models and procedures.…”
Section: Introductionmentioning
confidence: 99%